Measurement of beauty and charm production in deep inelastic scattering at HERA and measurement of the beauty-quark mass - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Arslan, O; Aushev, V; Aushev, Y; Bachynska, O; Barakbaev, A; Bartosik, N; et al. (Springer Verlag, 2014)
Abstract: The production of beauty and charm quarks in ep interactions has been studied with the ZEUS detector at HERA for exchanged four-momentum squared 5 < Q2< 1000 GeV2 using an integrated luminosity of 354 pb−1. The beauty and charm content in events with at least one jet have been extracted using the invariant mass of charged tracks associated with secondary vertices and the decay-length significance of these vertices. Differential cross sections as a function of Q2, Bjorken x, jet trans- verse energy and pseudorapidity were measured and compared with next-to-leading-order QCD calculations. The beauty and charm contributions to the proton structure functions were extracted from the double-differential cross section as a function of x and Q2. The running beauty-quark mass, mb at the scale mb, was determined from a QCD fit at next-to-leading order to HERA data for the first time and found to be mb(mb) = 4.07 ± 0.14 (fit)− 0.07+ 0.01(mod.)− 0.00+ 0.05(param.)− 0.05+ 0.08(theo.) GeV.